Variations in end-expiratory pressure during partial liquid ventilation : Impact on gas exchange, lung compliance, and end-expiratory lung volume - MANALIGOD, J. M; BENDEL-STENZEL, E. M; MEYERS, P. A; BING, D. R; CONNETT, J. E; MAMMEL, M. C (Chest, 2000)
To determine the effects of different levels of positive end-expiratory pressure (PEEP) during partial liquid ventilation (PLV) on gas exchange, lung compliance, and end-expiratory lung volume (EELV). Prospective animal study. Animal physiology research laboratory. Nine piglets. Animals underwent saline solution lavage to produce lung injury. Perflubron was instilled via the endotracheal tube in a volume estimated to represent functional residual capacity. The initial PEEP setting was 4 cm H(2)O, and stepwise changes in PEEP were made. At 30-min intervals, the PEEP was increased to 8, then 12, then decreased back down to 8, then 4 cm H(2)O. After 30 min at each level of PEEP, arterial blood gases, aortic and central venous pressures, heart rates, dynamic lung compliance, and changes in EELV were recorded. Paired t tests with Bonferroni correction were used to evaluate the data. There were no differences in heart rate or mean BP at the different PEEP levels. CO(2) elimination and oxygenation improved directly with the PEEP level and mean airway pressure (Paw). Compliance did not change with increasing PEEP, but did increase when PEEP was lowered. EELV changes correlated directly with the level of PEEP. As previously reported during gas ventilation, oxygenation and CO(2) elimination vary directly with PEEP and proximal Paw during PLV. EELV also varies directly with PEEP. Dynamic lung compliance, however, improved only when PEEP was lowered, suggesting an alteration in the distribution of perflubron due to changes in pressure-volume relationships.